Respuestas

2014-02-26T01:56:34+01:00
6x-(2x-5)≤3x+14<13-2(4-3x)
6x-2x+5 
≤ 3x+14 <13-8+6x Suma termino semejantes en todo los miembros
4x+5≤3x+14<5+6x             La dividimos en partes la ecuacion
4x+5≤3x+14                  ∧        3x+14<5+6x
4x-3x+5 ≤ 3x-3x+14                  3x-6x+14<5+6x-6x
x+5 ≤ 14                                  -3x+14<5
x+5-5 ≤ 14-5                             -3x+14-14<5-14 
x≤9                                            -3x<-9 
                                                     -x<-3 
                                                       x>3
sol.   3 < x ≤ 9

6x-(2x-5)≤3x+14<13-2(4-3x)            provemos x=5
30-(10-5)≤15+14<13-2(4-15)
30-5≤29<13-8+30
25≤29<35